O Sistema de Comunicação Digital (SICODI) como instrumento para efetivação do teletrabalho na fiscalização a cargo do Tribunal de Contas do Estado do Rio de Janeiro - Souza, Virgílio de Oliveira (2008)
The acts of public administration personnel are of great importance and various laws have been passed in attempt to limit the related expenses. The management of Public administration personnel is based on the principle of efficiency. The TCE/RJ (State of Rio de Janeiro/Audit Court) digital communication system is expected through telework to facilitate its auditing duties in compliance with the terms of the Federal and State constitutions. The TCE/RJ, the superior judicial body of auditing, has done more than just reduce costs and use flextime; it applies telework as an instrument to optimize public service through SICODI digital certification to maximize the resources applied to this constitutional act with greater efficiency for effective auditing. The focus of the first part of this study is to evaluate the tasks of positions that forward the TCE/RJ objectives and the profile characteristics of employees of the inspection area on personnel performance beginning with defined concepts and purposes. Questionnaires for auditors and technicians of the area were approved for this specific purpose to analyze the duties of positions and employee profiles. The second part of this study evaluates the TCE/RJ digital communication system according to theoretical reference and ISO/IEC Standard No. 9126-1, observing three dimensions: the content, usability and functionality. The results obtained, with the use of qualitative methods complemented by quantitative analysis, were positive for the implementation of telework in the inspection of personnel performance in relation to the analysts and technicians involved in this type of auditing as well as in relation to the TCE/RJ digital communication system.